Temperature effects on incidence of surgery for acute type A aortic dissection in the Nordics. Issue 1 (31st December 2022) - Oudin Åström, Daniel; Bjursten, Henrik; Oudin, Anna; Nozohoor, Shahab; Ahmad, Khalil; Tang, Mariann; Bjurbom, Markus; Hansson, Emma C; Jeppsson, Anders; Holdflod Møller, Christian Joost; Jormalainen, Miko; Juvonen, Tatu; et al.
ABSTRACT: We aimed to investigate a hypothesised association between daily mean temperature and the risk of surgery for acute type A aortic dissection (ATAAD). For the period of 1 January 2005 until 31 December 2019, we collected daily data on mean temperatures and date of 2995 operations for ATAAD at 10 Nordic cities included in the Nordic Consortium for Acute Type A Aortic Dissection (NORCAAD) collaboration. Using a two-stage time-series approach, we investigated the association between hot and cold temperatures relative to the optimal temperature and the rate of ATAAD repair in the selected cities. The relative risks (RRs) of cold temperatures (≤−5°C) and hot temperatures (≥21°C) compared to optimal temperature were 1.47 (95% CI: 0.72–2.99) and 1.43 (95% CI: 0.67–3.08), respectively. In line with previous studies, we observed increased risk at cold and hot temperatures. However, the observed associations were not statistically significant, thus only providing weak evidence of an association.